Nanoparticle uptake by airway phagocytes after fungal spore challenge in murine allergic asthma and chronic bronchitis - Geiser, Marianne; Mall, Marcus A. (BMC pulmonary medicine, 2014)
In healthy lungs, deposited micrometer-sized particles are efficiently phagocytosed by macrophages present on airway surfaces; however, uptake of nanoparticles (NP) by macrophages appears less effective and is largely unstudied in lung disease. Using mouse models of allergic asthma and chronic obstructive pulmonary disease (COPD), we investigated NP uptake after challenge with common biogenic ambient air microparticles.
Gesehen am 05.08.2020